Ziconotide Monotherapy: A Systematic Review of Randomised Controlled Trials - Brookes, Morag E.; Eldabe, Sam; Batterham, Alan (Current Neuropharmacology, 2017)
Introduction: Chronic neuropathic pain is difficult to treat and is often refractory to most modalities of treatment. Ziconotide is a novel, potent, non-opioid, calcium channel blocking agent which has been shown in clinical trials to be effective in treating chronic neuropathic pain. Methods: EMBASE, MEDLINE, CINAHL Plus and Web of Science electronic databases were searched for English language studies. Reference sections of articles were examined for further papers and the manufacturer of ziconotide was contacted for further unpublished data. Three randomised controlled trials in ziconotide monotherapy were included and subjected to a random effects meta-analysis. Results: All three studies used the similar main outcome measure (visual analogue scale of pain intensity; VASPI) and were therefore comparable. A Jadad score was performed for each paper. Frequent serious adverse events (SAEs) were observed which resulted in two of the studies revising the protocol. The metaanalysis revealed a pooled odds ratio (responders on ziconotide vs. placebo) of 2.77 (95% CI, 1.37 to 5.59). Discussion: The results suggest that ziconotide is beneficial for pain reduction in chronic neuropathic pain. However, there remain some methodological issues that may call into question the validity of the results. It is evident that more work needs to be conducted to further validate the efficacy of ziconotide and to discover new areas of use.
Keywords: ziconotide